Assessment tools for mapping learning outcomes with learning objectives - Sinha, G. R. (Hershey, USA : IGI global, 2021)
"This book explores practical assessment tools for mapping learning outcomes with learning objectives used in outcome-based education"--
Evaluating teaching competence for TESOL practicum : a case study of Vietnamese EFL student teachers / Trinh Ngoc Thanh -- Outcome-based education evolvement and modern way of implementation in current scenario / NIkhat Shama -- Objectives and learning outcomes / Cetin Toraman -- Learning objective and assessment linkage : its contribution for meaningful students learning / Abatihun Sewagegn -- Outcome based education in business schools : the adoption of a progressive cult / Priya Solomon, Ruchi Khandelwal -- Teaching and assessment of a course in outcome based education : attainment of course outcomes using direct and indirect methods / Durga Prasad Garapati, SM Padmaja -- Traditional teaching pedagogy-student versus teacher centric / Bhagwati Patel, Naveen Goel, Kkusumanjali Deshmukh -- Fractional choice based credit system : a learner centric approach / Prashant Borkar, Meenakshi Arya -- Challenges and best practices of outcome based education / Shankru Guggari, L. Ravikumar, Vinay ML Gowda -- Buddy pair approach as a tool to assess the efficacy of outcome based education / Meenakshi Arya, Prashant Borkar, Prasanna Devi -- Critical issues and answers of outcome-based education for technical Institutions in India / JP Patra, Alok Jain, Sumitra Samal -- Assessment of learning outcomes / Aysen Aytug Kosan.
Includes bibliographical references and index.
Keywords: Competency-based education -- India; Educational tests and measurements -- India